The use of kettle holes for reconstructing former soil cover in different types of land use - Kruczkowska, Bogusława (IGiPZ PAN, 2016)
The aim of the study was to identify and examine main directions of soil patterns, typology, SOC (Soil Organic Carbon) and Nt (Total Nitrogen) content in the topsoil changes that have occurred in kettle holes as an effect of soil erosion and anthropogenic denudation. Varied in the type of land use, three closed basins located in young glacial landscape in north-western Poland were investigated. According to the type of land use, the total area of soils with untransformed or moderately transformed morphology is different. Significant modifications have been taking place not only in mineral soils, which are located on slopes, but especially in soils of the bottom of sedimentary basins. In fact, most of primary soil properties and morphology have been replaced by new characteristics. The most intensive modifications of soil morphology and soil chemical properties occurs within croplands. Total area of colluvial soils can be treated as indicator of soil erosion processes intensity.
24 cm
Keywords: kettle holes; soil cover evolution; soil redistribution; soil morphology; soil chemical properties